2010
DOI: 10.1016/j.chemgeo.2010.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Barium isotope fractionation in the global barium cycle: First evidence from barium minerals and precipitation experiments

Abstract: In this study, we present first results from an ongoing investigation on the stable barium (Ba) isotope fractionation in the natural barium cycle. Stable Ba isotope signatures of international IAEA reference materials (synthetic barium sulfate, IAEA-SO-5, -6, and barium carbonate, IAEA-CO-9), natural Ba minerals and experimental Ba precipitates have been analyzed as a first approach to evaluate potential discriminating processes in the global geochemical barium cycle. Ba = − 0.5‰ was found in a diagenetic bari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
149
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(162 citation statements)
references
References 39 publications
9
149
3
1
Order By: Relevance
“…More negative Ba * in STUW are also associated with +0.1 ‰ increases in dissolved Ba isotope compositions relative to surface waters, consistent with the removal of isotopically-light Ba into BaSO 4 (e.g. Von Allmen et al, 2010). Such a pattern of more negative Ba * associated with heavier Ba isotope compositions in shallow subsurface waters is only expected if two conditions are met: if both the removal of Si and Ba are vertically segregated (e.g.…”
Section: Surface and Near-surface Cycling Of Bariummentioning
confidence: 75%
See 2 more Smart Citations
“…More negative Ba * in STUW are also associated with +0.1 ‰ increases in dissolved Ba isotope compositions relative to surface waters, consistent with the removal of isotopically-light Ba into BaSO 4 (e.g. Von Allmen et al, 2010). Such a pattern of more negative Ba * associated with heavier Ba isotope compositions in shallow subsurface waters is only expected if two conditions are met: if both the removal of Si and Ba are vertically segregated (e.g.…”
Section: Surface and Near-surface Cycling Of Bariummentioning
confidence: 75%
“…The direction of the d 138 Ba anomaly is opposite to that expected if the signature was a result of sinking barite, which would be expected to add Ba with an isotopic composition of~+0.3 ‰ (assuming that BaSO 4 precipitates are approximately À0.2 to À0.4 ‰ lighter than mesopelagic waters; e.g. Von Allmen et al, 2010;Horner et al, 2015;Cao et al, 2016). Instead, this Ba may be sourced from seafloor sediments, which would indicate possible Ba isotopic fractionation effects during sediment diagenesis.…”
Section: /134mentioning
confidence: 88%
See 1 more Smart Citation
“…A handful of recent studies have begun examining Ba-isotopic variability in nature, and have identified significant Ba-isotopic fractionation during mineral precipitation experiments (Von Allmen et al, 2010;Böttcher et al, 2012), between various CaCO 3 minerals (Pretet, 2014), and most recently in igneous rocks (Miyazaki et al, 2014). Theoretical predictions support the direction, though not the magnitude, of Ba-isotopic fractionation observed during low-temperature mineral precipitation, which may be related to Ba 2+ ion desolvation (Hofmann et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…This is observed for calcium and magnesium isotopes in calcite and magnesite, respectively (i.e. Tang et al, 2008;Pearce et al, 2012) and for Sr and Ba isotopes in calcite (Boehm et al, 2012;von Allmen et al, 2010). In contrast, increasing calcite precipitation rates produces a less negative Δ 26 Mg calcite-fluid fractionation, as it reduces the preferential incorporation of 24 Mg into the lattice.…”
Section: Introductionmentioning
confidence: 97%